Assessing the Impact of Mortuary Siting and Environmental Compliance on Human and Environmental Wellbeing in Nigeria (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This study assessed the impact of mortuary siting and environmental compliance on human and environmental wellbeing in Nigeria. With increasing urbanization and inadequate land use planning, mortuary facilities are often located near residential areas, schools, and water sources, raising significant public health and environmental concerns. The research draws on qualitative and quantitative data, including case studies from Lagos, Abuja, and other urban centers, to analyze patterns of mortuary distribution, levels of environmental compliance, and associated risks. Findings reveal that poor siting practices and weak adherence to environmental regulations contribute to pollution, psychological stress, and violations of cultural norms. Furthermore, institutional barriers such as regulatory gaps, corruption, and limited stakeholder involvement exacerbate the problem. The study concludes that comprehensive policy reforms, stronger regulatory enforcement, and the incorporation of environmental justice principles into planning processes are essential to safeguarding public health and promoting sustainable urban development in Nigeria.